Cloning, purification and characterization of human dentine matrix protein 1(DMP1) - Tarek El-Bialy; Dror Aizenbud; Hamid Sadeghi; Paul Scott; Itay Aizenbud (Elsevier, 2023)
Introduction: Human teeth are composed mainly of dentin, formed by the odontoblasts. Dentin matrix protein 1 (DMP1) is one of odontoblast differentiation's most important growth factors. Human DMP1 has yet to be completely identified or studied. This study aimed to clone and characterize human DMP1. Materials and methods: The DMP1 gene sequence was prepared and cloned by transfection of human 293 cells. Results: The recombinant DMP1 was purified and characterized. Conclusion: The results suggested its future use in dental tissue regeneration and tissue engineering.